Detection of glaucoma in the elderly using laser scanning tomography - Hawker, Matthew James (2008)
Primary open angle glaucoma is mostly prevalent in patients over 60 years. However, studies examining the role of laser scanning tomography in detecting glaucoma hitherto have employed non-population based data drawn from younger subjects. This study employed an elderly, Caucasian, population-based cohort (minimum age 65 years, n=721). All subjects underwent ophthalmological examination including Goldmann applanation tonometry, suprathreshold automated visual field test and Heidelberg retina tomography. Normality was defined as normal visual acuity, visual field and intraocular pressure. Perimetrically normal males were found to have significantly larger optic cups than females. Normative data were used to construct three diagnostic tests: Linear regression of rim area, RADAAR (rim area/disc area asymmetry ratio) and the optic disc hemifield test (comparison of the superior and inferior rim/disc area ratios in the temporal and nasal sectors). Specificities at the 99th limit of normality were 91.4%, 95.1% and 98.3% respectively. Sensitivity was assessed using a cohort of patients (n=58) with a new diagnosis of open angle glaucoma at the Queen's Medical Centre, Nottingham within the last two years. Sensitivities at the 99th limit of normality were 72.4%, 55.6% and 27.6% respectively. Applying the regression analysis bilaterally and RADAAR simultaneously generated a specificity of 83.0% and sensitivity of 88.9%. Inclusion of the optic disc hemifield test did not further increase sensitivity. Linear regression of rim area/disc area was found to be susceptible to non-linearity and heteroscedasticity, causing reduced specificity in bigger optic discs. Modeling the relationship separately for each disc area quartile overcame this limitation to produce a diagnostic test with constant accuracy. Whilst laser scanning ophthalmoscopy can discriminate glaucoma with reasonable accuracy, it is limited by disagreement in contour placement and poor image quality in the elderly. The combination of multiple statistical tests is not ideal - application of statistical shape analysis techniques may better employ the normative data.